Cell-specific transcriptional signatures of vascular cells in Alzheimer’s disease: perspectives, pathways, and therapeutic directions - Soumilee Chaudhuri; Minyoung Cho; Julia C. Stumpff; Paula J. Bice; Özkan İş; Nilüfer Ertekin-Taner; Andrew J. Saykin; Kwangsik Nho (Molecular Neurodegeneration)
Abstract Alzheimer’s disease (AD) is a debilitating neurodegenerative disease that is marked by profound neurovascular dysfunction and significant cell-specific alterations in the brain vasculature. Recent advances in high throughput single-cell transcriptomics technology have enabled the study of the human brain vasculature at an unprecedented depth. Additionally, the understudied niche of cerebrovascular cells, such as endothelial and mural cells, and their subtypes have been scrutinized for understanding cellular and transcriptional heterogeneity in AD. Here, we provide an overview of rich transcriptional signatures derived from recent single-cell and single-nucleus transcriptomic studies of human brain vascular cells and their implications for targeted therapy for AD. We conducted an in-depth literature search using Medline and Covidence to identify pertinent AD studies that utilized single-cell technologies in human post-mortem brain tissue by focusing on understanding the transcriptional differences in cerebrovascular cell types and subtypes in AD and cognitively normal older adults. We also discuss impaired cellular crosstalk between vascular cells and neuroglial units, as well as astrocytes in AD. Additionally, we contextualize the findings from single-cell studies of distinct endothelial cells, smooth muscle cells, fibroblasts, and pericytes in the human AD brain and highlight pathways for potential therapeutic interventions as a concerted multi-omic effort with spatial transcriptomics technology, neuroimaging, and neuropathology. Overall, we provide a detailed account of the vascular cell-specific transcriptional signatures in AD and their crucial cellular crosstalk with the neuroglial unit. Graphical Abstract Endothelial and mural cell types mediate dysregulated transcriptional pathways and cell-cell interactions in AD. The neurovascular unit (NVU) is composed of various cell types, including endothelial cells, mural cells (pericytes, smooth muscle cells), fibroblast neurons, microglia, and astrocytes. Dysregulated transcriptional pathways in AD involve multiple pathways, notably immune responses, and angiogenesis common to both endothelial and mural cells. Additionally, pathways involving neuroinflammation and amyloid clearance are prominent in endothelial cell types, while mural cells exhibit pathways related to growth factors, cytoskeletal remodeling and synaptic function. In addition, crosstalk within the NVU and gliovascular unit (GVU) is altered in AD, with altered cell-cell communication evident, with increased interactions between endothelial cells, pericytes, neurons, and microglia, and decreased interactions between endothelial cells, fibroblasts, astrocytes, and neurons. Figure created with BioRender.com. Abbreviations: AD, Alzheimer's disease; NVU, Neurovascular unit; CNS, Central Nervous System.